Understanding Food Inflation: Drivers, Impacts, And Policy Responses (International Journal of Food and Nutritional Sciences, 2022)
This paper investigates into the various causes of food inflation, portrayed from classical as well as current economic theories to give a comprehensive analysis. It studies monetary factors, global demand shifts, crude oil prices, and other macroeconomic variables, highlighting how these factors collectively lead to food prices. The analysis underscores the complex interdependencies between these factors, with monetary policy, money supply, and global economic conditions playing significant roles. Moreover, this paper observes regional price shocks and rising input costs, such as those related to energy and labor, which further contribute to the volatility of food prices. Beyond the economic mechanisms, the paper also reports the comprehensive social and economic insinuations of food price inflation, particularly in developing countries. It examines how increasing food prices aggravate poverty and depressingly impact welfare of the people, especially among low-income people who spend a major portion of their income on food. The review of literature reveals that food inflation not only affects individual consumption patterns but also has broader consequences for economic stability and social welfare. Consequently, the paper calls for carefully planned policy interventions that take into account the complex causes of food inflation and aim to protect vulnerable people from its negative effects.